2013
DOI: 10.1186/1475-2840-12-4
|View full text |Cite
|
Sign up to set email alerts
|

Transient decrease in serum potassium level during ischemic attack of acute coronary syndrome: Paradoxical contribution of plasma glucose level and glycohemoglobin

Abstract: BackgroundAlthough a decrease in serum potassium level has been suggested to be a fairly common observation in acute coronary syndrome (ACS), there have so far been no definitive reports directly demonstrating the transient potassium decrease (the potassium dip) during ischemic attack of ACS compared to stable phase in individual patients. To understand the pathophysiological significance of the potassium dip, we examined the changes in serum potassium level throughout ischemic attack and evaluated the clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
36
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 27 publications
6
36
0
Order By: Relevance
“…The patients who underwent coronary bypass surgery were excluded from the analysis of “Duration of hospital stay”, since the surgery affects the hospitalization period independently of the disease severity. When all of the study subjects were divided into two groups based on the median value of ΔK (<0.3 and ≥0.3), a higher incidence of MI relative to unstable angina pectoris, in association with a longer hospitalization period and higher peak CK level, was observed in patients with a larger ΔK (Table 6), consistent with the findings from our previous study [13]. We further investigated the association of ΔK with the disease severity and clinical course in the subjects divided into two groups based on quartiles of ΔK (S5 Table).…”
Section: Resultssupporting
confidence: 89%
“…The patients who underwent coronary bypass surgery were excluded from the analysis of “Duration of hospital stay”, since the surgery affects the hospitalization period independently of the disease severity. When all of the study subjects were divided into two groups based on the median value of ΔK (<0.3 and ≥0.3), a higher incidence of MI relative to unstable angina pectoris, in association with a longer hospitalization period and higher peak CK level, was observed in patients with a larger ΔK (Table 6), consistent with the findings from our previous study [13]. We further investigated the association of ΔK with the disease severity and clinical course in the subjects divided into two groups based on quartiles of ΔK (S5 Table).…”
Section: Resultssupporting
confidence: 89%
“…Concerning electrolytes and blood glucose level, the present finding revealed a decreased in serum potassium (K) level but within normal level with no significant difference was found between two groups regarding serum potassium (K) and sodium (Na). This may be justified to that decreasing K level lead to vasoconstriction and may always associated with the occurrence of acute coronary syndrome [33]. This result was in line with Madias (2000) [34] and Foo (2003) [35] who suggested that reducing serum potassium (K) was detected in patients with acute coronary syndrome.…”
Section: Discussionsupporting
confidence: 80%
“…We previously reported increased levels of aldosterone production/secretion from failing human hearts. Moreover, our recent study demonstrated that there is a transient decrease in serum potassium level during ischemic attacks of acute coronary syndrome, which is at least partially mediated through the activation of the aldosterone cascade (Sekiyama et al 2013). Although these clinical findings provide evidence for local cardiac aldosterone synthesis/actions, this issue remains very controversial, and in fact, some reports have offered negative findings regarding the question of local aldosterone synthesis in the heart (Gomez-Sanchez et al 2004, Fiebeler et al 2005, Chai et al 2010.…”
Section: Discussionmentioning
confidence: 90%